Association Between Platelet Levels and 28-Day Mortality in Patients With Sepsis: A Retrospective Analysis of a Large Clinical Database MIMIC-IV - Wang, Danni; Wang, Suning; Wu, Hao; Gao, Jiansheng; Huang, Kairong; Xu, Danhong; Ru, Huangyao (Frontiers in Medicine, 2022)
Background This research focused on evaluating the correlation between platelet count and sepsis prognosis, and even the dose-response relationship, in a cohort of American adults. Method Platelet counts were recorded retrospectively after hospitalization for patients admitted to Beth Israel Deaconess Medical Center’s intensive care unit between 2008 and 2019. On admission to the intensive care unit, sepsis patients were divided into four categories based on platelet counts (very low < 50 × 109/L, intermediate-low 50 × 109–100 × 109/L, low 100 × 109–150 × 109/L, and normal ≥ 150 × 109/L). A multivariate Cox proportional risk model was used to calculate the 28-day risk of mortality in sepsis based on baseline platelet counts, and a two-piece linear regression model was used to calculate the threshold effect. Results The risk of 28-day septic mortality was nearly 2-fold higher in the platelet very low group when compared to the low group (hazard ratios [HRs], 2.24; 95% confidence interval [CI], 1.92–2.6). Further analysis revealed a curvilinear association between platelets and the sepsis risk of death, with a saturation effect predicted at 100 × 109/L. When platelet counts were below 100 × 109/L, the risk of sepsis 28-day death decreased significantly with increasing platelet count levels (HR, 0.875; 95% CI, 0.84–0.90). Conclusion When platelet count was less than 100 × 109/L, it was a strong predictor of the potential risk of sepsis death, which is declined by 13% for every 10 × 109/L growth in platelets. When platelet counts reach up to 100 × 109/L, the probability of dying to sepsis within 28 days climbs by 1% for every 10 × 109/L increase in platelet count.